Does Ownership Structure Affect Risk Management? Evidence from an Emerging Economy, Kenya - Tarus, Thomas Kiptanui; Tenai, Joel K; Komen, Joyce (Journal of Accounting, Business and Finance Research, 2019)
The purpose of the research is to establish the impact of ownership structure on risk management among listed non-financial firms in the Nairobi Securities Exchange, Kenya. The panel research design was appropriate and the population comprised of all 67 listed firms. Based on the inclusion-exclusion criterion, 41 non-financial firms were chosen from 2010-2017 while data was analyzed using logistic regression. The statistical values revealed that (β = 0.297, p<0.05) ownership structure significantly and positively impacts risk management. The structure of owners in relation to shareholdings is more likely to play an essential part in hedging transactions as it improves the worth of their equities which translates to enhanced efficiency and thus maximizing their wealth. The study contributes to understanding the structure of ownership and risk management via the utilization of hedging tools to alleviate exposure levels.